Engaging Older Adults in Participatory and Intergenerational Design Teams and Processes: a systematic review of the current investigation - Amaro, Ana Carla (2022)
This paper presents the results of a systematic review of the literature (SRL) in the field of Participatory Design (PD), undertaken under the scope of LOCUS – Playful Connected Rural Territories. The project employs an ethnographically, participatory and agile approach to the process of co-designing, developing and evaluating an IoT system to support playful intergenerational engagement in exploring cultural heritage of Portuguese rural territories, by engaging inhabitants, stakeholders and visitors. The SRL aimed to understand how older adults have been integrated and engaged into technology PD teams and processes. This paper focus on the most used methodological approaches and participation methods, along with the challenges in integrating older adults and the strategies to overcome them, which are discussed in the light of project aims. / Cet article présente les résultats d'une revue systématique de la littérature dans le domaine du design participatif, effectuée dans le cadre du Projet LOCUS - Territoires ruraux connectés et ludiques. Le projet utilise une approche ethnographique, participative et agile du processus de co-design, développement et évaluation d'un système d’Internet des objets pour soutenir un engagement intergénérationnel ludique dans l'exploration du patrimoine culturel des territoires ruraux portugais, en impliquant les habitants, les parties prenantes et les visiteurs. La revue systématique de la littérature vise à comprendre comment les personnes âgées ont été intégrées et engagées dans des équipes et des processus de design participatif des technologiques. Cet article se concentre sur les approches méthodologiques et les méthodes de participation les plus utilisées, ainsi que sur les défis de l'intégration des personnes âgées et les stratégies pour les surmonter, qui sont discutés à la lumière des objectifs du projet.